Perbandingan Akurasi Model Eksponensial, Hiperbolik, dan Logistik dalam Peramalan Jumlah Penduduk Kota Surabaya - Marena, Jihan Tria; Oktafianto, Kresna (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2026)
Rapid urbanization is putting demographic pressure on Surabaya City, the hub of Eastern Indonesia's trade, industry, education, and economic growth. Planning for sustainable development requires precise population estimates. The purpose of this study is to evaluate and contrast how well three mathematical models of population growth—the logistic, exponential, and hyperbolic models—predict Surabaya City's population. The differential equations of each model are used to handle secondary data in the form of a time-series of population figures from 2014 to 2024. The Mean Absolute Percentage Error (MAPE) value is used to assess the model's accuracy. The findings indicate that the logistic model yields a MAPE of 0.0119190%, the hyperbolic model yields a MAPE of 1.25509879%, and the exponential value yields a MAPE of 1.240023%. The logistic model was selected as the best model for long-term projections since it was the most accurate and had the lowest MAPE. According to the logistic model forecast estimates, Surabaya City's population is expected to reach 3,244,200 in 2035. It is envisaged that city governments would be able to use the research's suggestions as a scientific guide when creating population-responsive sustainable development policies.